1997
DOI: 10.1093/rheumatology/36.9.1005
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of interferon alpha on colchicine-resistant familial Mediterranean fever attacks: a pilot study

Abstract: About a quarter of familial Mediterranean fever (FMF) patients have recurrent painful attacks of polyserositis despite regular colchicine treatment. There is no known alternative drug for colchicine-resistant cases. We had previously observed a patient with FMF whose painful attacks disappeared during the 6 month period of interferon alpha (IFN) treatment for his chronic hepatitis B. The objective of the present study was to investigate the possible beneficial effect of IFN on these episodes. Twenty-one consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 13 publications
0
22
1
1
Order By: Relevance
“…In colchicine-resistant patients, IFNα was reported to shorten the episode duration in addition to control the episodes (89). Nevertheless, in a double-blind controlled study performed by the same investigators, no beneficial effect of IFNα could be demonstrated (90).…”
Section: Treatmentmentioning
confidence: 99%
“…In colchicine-resistant patients, IFNα was reported to shorten the episode duration in addition to control the episodes (89). Nevertheless, in a double-blind controlled study performed by the same investigators, no beneficial effect of IFNα could be demonstrated (90).…”
Section: Treatmentmentioning
confidence: 99%
“…Interferon can clear pre-core promoter HBV infection and cure PAN. Considering the effectiveness of interferon on FMF and PAN; we preferred to give this agent in addition to conventional therapies with methylprednisolone and cyclophosphamide (8)(9)(10)(11)(12)(13). Likewise, our patient responded well to the addition of the interferon therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Recent reports suggest that interferon could be effective to control the symptoms in FMF patients which were resistant to colchicines (8,9). Patients with hepatitis-related vasculitis including PAN respond to interferon therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that BMT should be considered, albeit as a last resort, in patients who are extremely unresponsive to all therapies including colchicine and interferon ␣. 34 …”
Section: Discussionmentioning
confidence: 99%